2014
DOI: 10.1016/j.yjmcc.2013.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ICa by basal PKA activity is facilitated by caveolin-3 in cardiac ventricular myocytes

Abstract: L-type Ca channels (LTCC), which play a key role in cardiac excitation–contraction coupling, are located predominantly at the transverse (t-) tubules in ventricular myocytes. Caveolae and the protein caveolin-3 (Cav-3) are also present at the t-tubules and have been implicated in localizing a number of signaling molecules, including protein kinase A (PKA) and β2-adrenoceptors. The present study investigated whether disruption of Cav-3 binding to its endogenous binding partners influenced LTCC activity. Ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 27 publications
11
79
1
Order By: Relevance
“…Although both PKA and CaMKII have previously been shown to contribute to the basal regulation of ventricular I CaL , particularly at the t-tubule membrane (7)(8)(9)12), basal I CaL in atrial myocytes from either sham control or failing hearts in the present study was insensitive to inhibition of PKA or CaMKII. Notably, the absence of regulation of basal atrial I CaL by PKA in CAL hearts in the present study contrasts markedly with the increased PKA-dependent regulation of basal I CaL at the t-tubule of ventricular myocytes reported recently from the same hearts (9).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Although both PKA and CaMKII have previously been shown to contribute to the basal regulation of ventricular I CaL , particularly at the t-tubule membrane (7)(8)(9)12), basal I CaL in atrial myocytes from either sham control or failing hearts in the present study was insensitive to inhibition of PKA or CaMKII. Notably, the absence of regulation of basal atrial I CaL by PKA in CAL hearts in the present study contrasts markedly with the increased PKA-dependent regulation of basal I CaL at the t-tubule of ventricular myocytes reported recently from the same hearts (9).…”
Section: Discussioncontrasting
confidence: 66%
“…We have previously reported that left ventricular ejection fraction was reduced by 50% and left ventricular end-diastolic volume was increased by more than 100% in CAL compared with Sham for this group of animals (9). Atrial myocytes were isolated using our standard methods (6,8), following rapid excision of the heart under pentobarbital anesthesia. Isolated myocytes were stored for 2-10 h before use on the day of isolation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rather than a direct interaction between Cav3 and Ca v 1.2 (the ion channel subunit of LTCCs) it is thought that Cav3 serves to sequester PKA bringing it in close proximity to the ion channel and a number of proteins involved in the β 2 AR/cAMP pathway to form a macromolecular signalling complex. Building upon this study, Orchard and colleagues (Bryant, et al, 2014) have recently shown that disruption of Cav3 leads to a decrease in the amplitude of the calcium current in response to β 2 -adrenergic stimulation, linking Cav3 to PKA activity. However, the depression of I Ca,L was not consistent with perturbation of only a small sub-population of LTCCs, suggesting that this signalling pathway may have implications for LTCCs within the t-tubules and hence E-C coupling.…”
Section: Populations Of E-c Coupling Proteins Are Regulated By Caveolmentioning
confidence: 70%
“…Furthermore, this increase is can be reversed by calcineurin inhibition but not PKA inhibition [167, 168]. The finding that PKA activation of I Ca,L is specific to T-tubules and is lost upon detubulation might explain this discrepancy [164, 169, 170]. One possibility is that modification of I Ca,L by calcineurin occurs throughout the cell but is masked by the opposing action of PKA in T-tubules.…”
Section: Calcineurin Substrates Relevant To Cardiovascular Healthmentioning
confidence: 99%